Research on the Protective Effects of Different Chinese Medicine Compounds on Gefitinib-Induced Hepatotoxicity - Yin, Xiaoting; Li, Min; Li, Yucheng (Chinese medicine and natural products, 2024)
Objective Our objective was to screen drugs with good protective effects on gefitinib-induced hepatotoxicity.Methods Fifty-four specific pathogen-free-grade male mice of the Institute of Cancer Research were randomly divided into a normal group, gefitinib group, glutathione group, ligustrazine group, silymarin group, glycyrrhizic acid group, baicalin group, paeoniflorin group, and matrine group, with six mice in each group. Except for the normal group, the remaining groups of mice were intragastrically administered 400 mg·kg−1 of gefitinib for 16 days to induce liver injury. Mice in each treatment group were intragastrically administered 100 mg·kg−1 of the corresponding drug 30 minutes after gefitinib administration each day. The normal group and model group mice were intragastrically administered with an equal volume of 0.5% carboxymethylcellulose sodium (CMC-Na), and the administration volume was 10 mg·kg−1. Then, 30 minutes after the last administration, blood was collected from the retro-orbital venous plexus, and the mice were killed by cervical dislocation to obtain liver weight and calculate the liver index. Liver pathological changes were observed by hematoxylin–eosin (HE) staining; the levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) in serum were detected using biochemical kits. AML12 cells were cultured in a medium containing drugs for 30 minutes. Except for the normal group, the remaining groups were induced cell damage with 20 μmoL·L−1 gefitinib for 24 hours. Cell viability was detected using a cell counting kit-8, and the levels of ALT, AST, and lactate dehydrogenase (LDH) in the cell culture supernatant were measured using biochemical kits.Results Animal experiments showed that compared with the gefitinib group, glycyrrhizic acid and baicalin significantly increased the body weight of mice (p < 0.01) and decreased the liver index and levels of ALT and AST (p < 0.05); ligustrazine and silymarin significantly increased the body weight of mice (p < 0.01) and decreased the level of AST (p < 0.05); paeoniflorin and matrine significantly decreased the levels of ALT and AST (p < 0.01). HE staining showed that the liver tissue of mice in the gefitinib group presented a large number of inflammatory cell infiltrations and disordered arrangement of hepatic cords; glutathione, glycyrrhizic acid, baicalin, paeoniflorin, and matrine significantly alleviated pathological damage to mouse liver tissue. Cell experiments showed that all drugs could alleviate gefitinib-induced damage to AML12 cells to varying degrees, among which glycyrrhizic acid, baicalin, and paeoniflorin had better protective effects, with cell survival rates increased to 96.4, 81.1, and 78.2%, respectively. Compared with the gefitinib group, glycyrrhizic acid significantly reduced the levels of ALT, AST, and LDH (p < 0.05); silymarin, baicalin, and paeoniflorin significantly reduced the levels of ALT and LDH (p < 0.05).Conclusion Glycyrrhizic acid, baicalin, and paeoniflorin all have good protective effects against gefitinib-induced hepatotoxicity, among which glycyrrhizic acid has the best effect.
Keywords: hepatotoxicity; gefitinib; hepatoprotective effect; traditional Chinese medicine; glycyrrhizic acid